Pengaruh Kepemimpinan, Pendidikan, Perencanaan Kerja Dan Pengawasan Terhadap Prestasi Kerja Pegawai Sekretariat Dprd Kabupaten Empat Lawang - Susanti, Yurna; Aprini, Nisma; Batara, Ivan (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research aims to determine and analyze the influence of leadership, education, work planning and supervision individually and jointly on the work performance of employees of the Empat Lawang Regency DPRD Secretariat. The research method used in this research is a quantitative method using questionnaires distributed to respondents. Test data quality using validity tests, reliability tests and normality tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial simultaneous tests and coefficient of determination. The results of the analysis show that leadership, education, work planning, and supervision have a significant influence, individually and collectively, on the work performance of employees of the Empat Lawang Regency DPRD Secretariat